Enhancing Cross-Cultural Understanding Among ASEAN Youth - Muhammad Rizky Andis Rafaldhanis; Yunita Fajarani; Arya Dimas Kartanapura (Program Studi Hubungan Internasional FISIP Universitas Jayabaya, 2023)
ASEAN is known for its diverse cultural heritage, containing many languages, traditions and customs. In this region, intercultural understanding among ASEAN youth is very important because it can promote harmony, cooperation and mutual respect among member countries. This article examines the effectiveness of programs that promote intercultural understanding among ASEAN youth. Important programs such as student exchange programmes, intercultural dialogue and cultural festivals are powerful tools for bridging gaps and strengthening intercultural understanding. Discussions and meetings of young people from various ASEAN countries give them the opportunity to exchange opinions, find solutions and understand different cultural perspectives. Digital platforms and social media play an important role in facilitating intercultural interactions. There are several recommendations to increase intercultural understanding among ASEAN youth that can be implemented in various ways that are inclusive and sustainable, namely integrating intercultural education into the formal curriculum, expanding exchange programs, and using digital technology for virtual interactions. One of the initiatives that represent this is ASCC (ASEAN Socio-Cultural Community), a platform for development in various areas of life such as education, sports, health, social and women's issues, and AYC (ASEAN Youth Cultural Forum). ), an annual event that brings together young people from across the ASEAN region to promote cultural understanding and cooperation. The forum serves as a forum for young people to discuss, share experiences and present their own culture. By implementing these strategies, ASEAN countries can foster mutual respect, cooperation and solidarity among ASEAN's younger generation.